Between terror and religion: paving ways to silencing arms in the north-eastern region of Nigeria - Bamidele, Seun (Penerbit Universiti Kebangsaan Malaysia, 2017)
The growing influence of the insurgent group known as Boko Haram is a worrisome prospect for Nigeria. It appears that the insurgent landscape of the country will become more complex and threatening after the emergence of the Shekau Bin Abubakar-led Boko Haram insurgent group in the north-eastern region. Because Nigerian insurgents do not operate in isolation, it is natural for them to draw inspiration from the IS. As insurgent group prepare to enter into another phase of ideologically and operationally transformed jihadist discourse, the implications for Nigeria’s internal security are severe. Apart from security implications, this process will affect extremism discourse in the country and the behaviour of non-violent religious organisations. This article will explore how the widespread use of arms in Nigeria’s north-eastern region aggravates the problem of the safety and security of lives and property, undermining stable peace. It also suggests ways by which the critical challenges posed to human security in the region can be tackled in order to realise genuine religious tolerance and peace everywhere in the north-eastern region.